Liquid level sensing device - Maziyah, Mat Noh (2003)
The project designed to be implemented to measure the level of molten iron liquid inside a tank. The design is based on a torque-controlled drive where the level of the liquid in the tank is measured using a suspended float. The float is lowered from the disc drilled around its perimeter and a lightweight rope, using torque sensitive electric drive and rotary encoder circuit to produce the pulse that is used to calculate the level of the liquid inside a tank. When the float makes contact with the liquid level surface, the torque reduces and the number of revolutions made by the disc is counted and the level is calculated using an appropriate formula and displayed.